Diversidad genética y relaciones de parentesco de las poblaciones silvestres y cultivadas de pejibaye (Bactris gasipaes, Palmae), utilizando marcadores microsatelitales - Alfredo Hernández Ugalde, José (2008)
The genetic diversity of the peach palm (Pejibaye, Bactris gasipaes Kunth) was evaluated using four nuclear DNA microsatellites in an effort to elu-cidate the evolution and domestication of this crop. A total of 258 samples from seven wild populations and eleven races were analyzed. All loci were polymorphic and a total of 50 alleles were identified. Average genetic diversity (0.67) and genetic differentiation among populations (Fst=0.16) were high when all populations were considered. Genetic differentiation was lower when the populations were grouped according to their origin into Western and Eastern populations (Fst=0.13 for both). Gene flow was slightly higher among Western popula-tions (Nm=1.71) than among Eastern populations (Nm=1.62). The Putumayo, Yurimaguas, vaupés, Tucurrique and Guatuso races seem to have been subjected to intense human selection. Hybrid populations exist in Azuero, Tuira, Cauca, vaupés, Puerto Ayacucho and Solimões, probably resulting from exchange and introgressions among sympatric wild and cultivated populations. Genetic distance (Dm) was estimated to determine the degree of relationship among populations using the neighbor-joining method; the wild populations from Maracaibo were used as the outgroup. The populations were divided into three general groups: Maracaibo (B. caribaea, B. macana var veragua and B. macana var arapuey), Eastern Amazon (Tembe, Pará and Acre) and a third group with two subgroups, Western (Azuero, Chontilla, Tuira, Cauca, Tucurrique and Guatuso) and Upper Amazon (B. dahlgreniana, Puerto Ayacucho, Solimões, vaupés and Putumayo). The genetic relationships strongly sup-port the hypothesis that peach palm was brought into cultivation independently in no less than three areas: the Western Andes (extending into lower Central America); Upper Amazon (extending into the Solimões and its tributaries), and the Eastern Amazon (extending from Bolivia to the lower Amazon through the Madeira River).